Doped sodium aluminium hydrides as hydrogen storage materials- characterizations and mechanistic insights - Fu, Q; Tsang, S (2005)
The dehydriding and rehydriding of sodium aluminium hydride, NaAlH 4, is kinetically enhanced and rendered reversible in the solid state upon doping with a small amount of catalyst species, such as titanium, zirconium or tin. The catalyst doped hydrides appear to be good candidates for development as hydrogen carriers for onboard proton exchange membrane (PEM) fuel cells because of their relatively low operation temperatures (120-150°C) and high hydrogen carrying capacities (4-5 wt.%). However, the nature of the active catalyst species and the mechanism of catalytic action are not yet known. In particular, using combinations of Ti and Sn compounds as dopants, a cooperative catalyst effect of the metals Ti and Sn in enhancing the hydrogen uptake and release kinetics is hereby reported. In this paper, characterization techniques including XRD, XPS, TEM, EDS and SEM have been applied on this material. The results suggest that the solid state phase changes during the hydriding and dehydriding processes are assisted through the interaction of a surface catalyst. A mechanism is proposed to explain the catalytic effect of the Sn/Ti double dopants on this hydride.